The new insights of 2015 ESC Pulmonary Hypertension Guidelines - Mehmet Serdar Küçükoğlu; Ümit Yaşar Sinan (KARE Publishing, 2016)
2015 European Society of Cardiology and European Respiratory Society Pulmonar Hypertension guideliene was announced in August in 2015 ESC meeting. According to this guideline, pulmonary hypertension was defined as pathophysiological disease that includes more than one clinical situation and can make it more complicated to most of respiratory diseases. We aimed to introduce the innovations that is brought to our daily practice by new guidelines.